2011
DOI: 10.1002/term.429
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β3 regulates assembly of a non-fibrotic matrix in a 3D corneal model

Abstract: Purpose Corneal tissue engineering has attracted the attention of many researchers over the years in part due to the cornea’s avascularity and relatively, straight forward structure. However, the highly organized and structured nature of this optically clear tissue has presented a great challenge. We have previously developed a model where human corneal fibroblasts (HCFs) are stimulated by a stable Vitamin C (VitC) derivative to self-assemble an extracellular matrix (ECM). Addition of TGF-β1 enhanced the assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
144
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(163 citation statements)
references
References 53 publications
16
144
0
3
Order By: Relevance
“…At the end of the experimental period, the constructs were examined for the expression of intracellular and extracellular components, which are indicators of a normal or fibrotic corneal fibroblast phenotype. 25,43,44 We found that PHCFs on both substrates produced markers consistent with a normal, nonfibrotic culture system (Fig. 6).…”
Section: Ecm Synthesissupporting
confidence: 58%
“…At the end of the experimental period, the constructs were examined for the expression of intracellular and extracellular components, which are indicators of a normal or fibrotic corneal fibroblast phenotype. 25,43,44 We found that PHCFs on both substrates produced markers consistent with a normal, nonfibrotic culture system (Fig. 6).…”
Section: Ecm Synthesissupporting
confidence: 58%
“…6,24 TGF-b1 induces fibroblastic and myofibroblastic differentiation by stimulating cell stratification and matrix component production, while increasing fibrotic protein marker expression 36 such as a-SMA, which was confirmed by immunohistochemical data. The action of TGF-b1 was very potent in that it blocked epithelial cell proliferation (data not shown) while stimulating the proliferation and re-activation of the stromal cells.…”
Section: Stromal Cells Retain Their Plasticity In 2d and 3dmentioning
confidence: 68%
“…The TGF-b3 was most effective to induce the stromal matrix without expression of fibrotic markers. 16 These findings suggest an effective way to reproduce native corneal stromal tissue with growth factor manipulation. In this report, the effects of FGF-2 and TGF-b3, individually and together, are combined with a highly aligned fibrous substrate in an effort to generate corneal stromal tissue constructs that reflect the structural organization and composition of native tissue, and that are of dimensions that might be considered for further implementation in animal models.…”
Section: Introductionmentioning
confidence: 84%
“…36 The TGF-b3 isoform is responsible for scarless healing of fetal wounds in which the collagen organization is maintained, suggesting it has an in vivo biological role distinct from the other two isoforms. 37 Recently, Karamichos et al 16 systematically compared the influence of three isoforms of TGF-b on the expression of fibrotic markers and ECM production by human corneal fibroblasts in an in vitro model. Unlike TGF-b1 and TGF-b2, low concentrations of TGF-b3 (0.1 ng/mL) suppressed the expression of fibrotic markers type III collagen and a-SMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation